Tailoring the microstructure and mechanical properties of Cu–Fe alloy by varying the rolling path and rolling temperature - Jing Xu; Bo Guan; Rui Fu; Yang Wu; Qiang Hu; Jin Zou; Guojie Huang; Changjian Yan (Journal of Materials Research and Technology, 2023)
Cu–Fe alloys are expected to be extensively used in electronics, transportation and machinery industries due to the extraordinary mechanical properties and functional properties. To optimize rolling process and the final properties of Cu–Fe plates. The effect of rolling path, rolling temperature and thickness reduction on microstructure evolution, mechanical and electrical properties of Cu–Fe alloy are carefully investigated. The results shown that the thickness reduction has a significant effect on mechanical properties of Cu–Fe alloy. The yield strength of Cu–Fe plates with 20% thickness reduction is more than 2 times higher than that of homogenized ingot. While the yield strength increases gradually as further increasing the thickness reduction. Rolling temperature is an important parameter determining the strength-ductility balance. The strength of plate rolled with 80% thickness reduction at 400 °C is similar to that of the plates in cold-rolled state, and the ductility is higher than that for the plates in the cold-rolled state. Further investigation reveals that the formation of heterogeneous structure characterized with recrystallized-fine grains embedded in deformed-coarse grains is responsible for the observed extraordinary mechanical properties. Rolling path could also affect the microstructure evolution and formability of the plates. For plate rolled with route 1 (unidirectional rolling), a stronger Copper-type texture with two Brass-type textures are observed. For plate rolled with route 2, where the rolled plate is rotated to 90° with respect to previous rolling direction between adjacent rolling passes, only Brass-type texture is generated. A rolling-path dependent edge-crack behavior is observed during rolling. Edge cracks are generated during rolling with route 2, while the edge cracks are not observed for plates rolled with route 1. Factors affecting the edge-cracks behavior are also discussed.